An Assessment of the Production and Marketing of Onions in Barbados - Instituto Interamericano de Ciencias Agrícolas (IICA) (Instituto Interamericano de Ciencias Agrícolas (IICA), 2020)
An investigation is made of the present state of onion production and marketing together with the problems encountered in recent years. Against the background of this assessmant, a number of initiatives area suggested which could be introduced to increase-domestic self-sufficiency as well as increasing exports within the Caribbean region